1948
DOI: 10.1038/icb.1948.54
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis Following Electrically Induced Convulsions

Abstract: The application in this hospital of alternating current for electro-convulsive therapy (E.C.T.) and electronarcbsis in certain mental disturhances afforded the opportunity of investigating the effects of this form of therapy on some of the components of the hlood. Schiitz (1942) ohserved in vitro a delayed coagulation of blood following application of a weak direct current.Brecht and Kummer (1943) noted a leucocytosis immediately after electrical shock; there was no alteration of hlood sugar or protein.Spiege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

1952
1952
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
1
18
0
2
Order By: Relevance
“…The various experiments which have been described would appear to reconcile the contradictory reports of Christensen (1) and of Fantl and his associates (2,3). The digestion of both fibrinogen and fibrin by the plasma proteolytic enzyme results principally in the breakdown of the molecule whose molecular weight is approximately 400,000 to 700,000 to molecules whose molecular weight is approximately 100,000 (7).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…The various experiments which have been described would appear to reconcile the contradictory reports of Christensen (1) and of Fantl and his associates (2,3). The digestion of both fibrinogen and fibrin by the plasma proteolytic enzyme results principally in the breakdown of the molecule whose molecular weight is approximately 400,000 to 700,000 to molecules whose molecular weight is approximately 100,000 (7).…”
Section: Discussionmentioning
confidence: 41%
“…When either plasma or serum mixed with fibrinogen was diluted with buffer, and optimal amounts of streptokinase were added, the proteolytic enzyme was activated whether or not the fibrinogen had been clotted by thrombin. (3) The time required for the spontaneous digestion of fibrinogen and fibrin in oxalated plasma Fantl and Simon (2) reported that the clotted plasma of patients who had been given electric shock therapy underwent fibrinolysis before appreciable digestion of fibrinogen was noted. If this were the case, then one might infer that the spontaneous activation of the plasma proteolytic The relative effect of streptokinase upon the digestion of fibrinogen and fibrin in human serum Time required for digestion of (a) fibrin, in a mixture of 0.1 ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory activity of plasma against the plasma proteolytic enzyme was tested against purified bovine plasma proteolytic enzyme. 4 The enzyme was dissolved in buffer and standardized in the following manner: The enzyme solution was serially diluted with buffer, 0.3 ml. of each dilution was pipetted into pyrex tubes (internal diameter, 8 mm.)…”
Section: Methodsmentioning
confidence: 99%
“…Abnormally rapid fibrinolysis has been observed in blood drawn from patients with a wide variety of diseases (1)(2)(3). Rapid fibrinolysis has also been seen in the blood of patients undergoing electric shock therapy (4), and in patients with shock as the result of burns or hemorrhage (5).…”
mentioning
confidence: 99%